The Effects of Group Sizes on Behaviors, Meat Characteristics and Growth Performance of Growing and Finishing Pigs Under Tropical Conditions in Thailand - Wiyabot, Thunwa (Asian Health, Science and Technology Reports, 2018)
The objectives of this study was to evaluate the effect of group size on growth performance of growing and finishing pigs under tropical conditions in Thailand. The group sizes were 4, 8, and 12 pigs per pen, providing a floor allowance of 1.50, 0.75, and 0.51 m2/pig, respectively. The pigs that were reared in a group size of 12 pigs per pen ate, drank, walked, mouth piped, rooted the floor, rooted the pipe and pawed more significantly often (P<0.05) than did the pigs that were reared in group sizes of 4 and 8 pigs per pen. These feeding behaviors and the high temperature of Thailand caused high rectal and skin temperatures, which were the highest in the group size of 12 pigs per pen. Moreover, the high temperature and the increased group size may cause heat stress, which would decrease the average daily gain (ADG). The largest group size of 12 pigs per pen presented the lowest ADG in both growing and finishing phases, which significantly differed (P<0.05) compared to the group sizes of 4 and 8 pigs per pen. In addition, the high temperature and the feeding frequency in the group sizes of 8 and 12 pigs per pen provided a better back fat thickness that was significantly less than that of the group size of 4 pigs per pen (P<0.05). So the appropriate group sizes and floor allowance for feeding growing and finishing pig were 8 pigs per pen or 0.75 m2 due to the high rate of ADG and the thinner back fat thickness (P < 0.05)